The effect of the perceived coach motivational climate and moral decision-making: A study among university football players - Mohd Zain, Nurul Sabrina; Ahmad, Mohamad Firdaus; Zulaikha Safwan, Nur Syazwani (Journal of Islamic, Social, Economics and Development, 2025)
The motivational climate created by coaches refers to the player's perception of the environment created by their coach. Coaches establish a motivational climate by shaping norms, fostering effective communication, and demonstrating actions that can affect how players act towards each other in football. The objectives of this study were to identify the main perceived coach motivational climate and the effect of perceived coach motivational climate on moral decision-making among Institutions of Higher Learning Football League players. This study was carried out on 195 football players in Division 1 from 13 university teams. The findings showed that players primarily perceive the coach motivational climate as a mastery climate, and there is a significant effect of perceived coach motivational climate on attitudes to moral decision-making among Institutions of Higher Learning Football League team players (B = 0.534, t = 4.611, p < 0.05). From the findings, it is proven that perceived coach motivational climate influences attitudes toward moral decision-making. The study can offer crucial insights that can guide future research for developing an entirely new typology within the research domain. Overall, further research is needed to fully understand how a specific coach's motivational climate can influence player perceptions of moral decision-making and ethical behaviour.